2020
DOI: 10.1093/braincomms/fcaa224
|View full text |Cite
|
Sign up to set email alerts
|

Altered white matter microstructure is related to cognition in adults with congenital heart disease

Abstract: Adults with congenital heart disease are at risk for persisting executive function deficits, which are known to affect academic achievement and quality of life. Alterations in white -matter microstructure are associated with cognitive impairments in adolescents with congenital heart disease. This study aimed to identify microstructural alterations potentially associated with executive function deficits in adults with congenital heart disease. Diffusion tensor imaging and tract-based spatial statistics were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 77 publications
3
27
0
Order By: Relevance
“…Thus, lower FA in CHD patients may provide evidence for alterations in the white matter microstructure but not for specific properties underlying these alterations. Previous studies have demonstrated that altered white matter microstructure in CHD is not restricted to the CST but is a rather global trait evident across the whole brain ( Brewster et al, 2015 , Ehrler et al, 2021 , Ehrler et al, 2020 , Rollins et al, 2014 , Watson et al, 2018 ), which can already be detected postnatally and is associated with decreased oxygen delivery ( Karmacharya et al, 2018 , Kelly et al, 2019 ). Of note is that two previously conducted studies in adolescents with CHD did not find any significant difference in FA of the CST compared to controls, while there was significantly lower FA in other major tracts ( Easson et al, 2020 , Watson et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, lower FA in CHD patients may provide evidence for alterations in the white matter microstructure but not for specific properties underlying these alterations. Previous studies have demonstrated that altered white matter microstructure in CHD is not restricted to the CST but is a rather global trait evident across the whole brain ( Brewster et al, 2015 , Ehrler et al, 2021 , Ehrler et al, 2020 , Rollins et al, 2014 , Watson et al, 2018 ), which can already be detected postnatally and is associated with decreased oxygen delivery ( Karmacharya et al, 2018 , Kelly et al, 2019 ). Of note is that two previously conducted studies in adolescents with CHD did not find any significant difference in FA of the CST compared to controls, while there was significantly lower FA in other major tracts ( Easson et al, 2020 , Watson et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sample 2 includes adult patients with different types of CHD, who were treated at the outpatient clinic of the University Hospital Zurich, Switzerland (for details see ( Ehrler et al, 2021 )). Sixty-six patients agreed to participate in the study, of whom 46 patients underwent an MRI scan.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As the population with Fontan circulation ages, further research is needed to assess the translation of neurodevelopmental and behavioral findings in childhood and adolescence into neurocognitive function in adulthood. Recent studies show that adults with CHD are at risk for persisting neurocognitive deficits, particularly in the domain of executive functions ( 69 ), which may alter their professional and personal achievement and quality of life. These deficits seem correlated to alterations of white matter microstructure in subjects with severe CHD, suggesting long-lasting neurological effects of critical CHD for some adults.…”
Section: Neuropsychological and Behavioral Outcomes Throughout The Li...mentioning
confidence: 99%